Development and validation of a questionnaire for professionalism in cyber users in medical sciences in Iran - Leili Mosalanejad; Saeed Abdollahifard (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Considering the importance of virtual professionalism and professional ethics in medical sciences, and the necessity to pay attention to this issue and its impact on medical professionalism, this study aimed to build a professional culture questionnaire in a virtual environment for students of medical sciences in Iran. MATERIALS AND METHODS: This is an exploratory, sequential, mixed-methods research which was conducted in three sections. In the first section, the concept of e-professionalism in medical sciences was analyzed using the hybrid concept analysis in the theoretical work, field work, and final analysis stages in order to extract information related to the concept. In the second section, an item of the questionnaire was designed based on the concept, reviewed texts, and related questionnaires, in the third section, psychometric properties of a questionnaires were evaluated. RESULTS: Totally, 39 items were included in the initial pool, which reduced to 33 items in the final questionnaire after reviewing the psychometric properties. Factor analyses led to extraction of five factors including appraisal of e-professionalism compliance with the laws and regulations governing cyberspace, individual professionalism, knowledge management, respect for professionalism in interpersonal and group rules, and complying with ethics in the use of cyberspace. The internal consistency of questionnaire was also confirmed by Cronbach's alpha coefficient of 0.78, also all factor correlations absed stability were significant (P < 0.05). CONCLUSION: An exploratory sequential study in this study led to the extraction of five factors and development of a 33-item questionnaire in e-professionalism. As results and analysis of the psychometric properties and validation of each item, this questionnaire is valid and reliable for the assessment of levels of e-professionalism in medical sciences in Iran.